The duration of the cortisol awakening pulse exceeds sixty minutes in a meaningful pattern. (July 2019) - Benz, Annika; Meier, Maria; Mankin, Mara; Unternaehrer, Eva; Pruessner, Jens C.
Highlights: The first cortisol pulse after awakening is longer than 60 min in the majority of subjects. A measurement period of 120 min after awakening is recommended to capture the entire duration of the first pulse in the majority of subjects. Amplitude and duration of the first two cortisol pulses after awakening are systematically associated with sex and menstrual cycle phase in women. While the first pulse is negatively related to the second pulse, the second pulse is positively associated with the third pulse. Up to five pulses can be observed during the first 270 min after awakening with high inter- and intraindividual variability. Abstract: The cortisol awakening response (CAR) is a well-established biomarker for the integrity of the hypothalamic-pituitary-adrenal (HPA) axis in healthy as well as clinical samples. Cortisol rise during the first 60 min after awakening is often used as a proxy of HPA axis regulation in health and disease. Ultradian pulsatility of cortisol is known to superimpose its circadian rhythmicity with the CAR being the first rise after awakening. However, the exact length of the complete first pulse (rise and fall) after awakening, as well as the association between the CAR, the complete first pulse, and successive ultradian pulses, has not yet been studied systematically. Aim of this study was to investigate cortisol dynamics after awakening beyond the standard assessment duration of 60 min in order to assess the cortisol awakening pulse, in relation to ultradian rhythmicity of cortisol after awakening. In a sample of 51 healthy participants, salivary cortisol was collected for the first 270 min after awakening in intervals of 30 min, on two separate days. Different parameters describing individual cortisol pulses over time with respect to inter- and intraindividual variations such as duration, amplitude and area under the curve (AUC) were calculated. Special emphasis was put on the first rise and fall after awakening, called the cortisol awakening pulse (CAP). Mean duration of the CAP was 108 min with high interindividual differences. Duration of first and second pulse were associated with subject's sex and menstrual cycle status, with a longer first pulse and an attenuated second pulse in male and female subjects in the luteal phase, compared to female subjects in the follicular phase, or women taking oral contraceptives. These results point to the potential usefulness of a longer sampling period for assessing ultradian pulsatility of cortisol in the morning, especially the CAP. To assess the complete pulse rather than the rise alone, measurement of cortisol levels after awakening for 120 min is recommended.